2022
DOI: 10.1002/batt.202200298
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Solubility of Redox‐Active Organic Species in Aqueous Redox Flow Batteries: A Review

Abstract: Redox flow batteries (RFB) have emerged as one of the most promising technologies for large-scale energy storage owing to their high safety, long operation life, and decoupled design of energy and power. However, the problems of high cost and low energy density restrict their further development. The cost merit and tunable structure of organic redox-active materials have prompted the development of organic RFBs. The solubility of the redoxmer is recognized as a parameter that contributes directly to the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…Encouraged by these results, we proceeded to study the structure–property relationships for this class of anolytes in order to identify next-generation derivatives based on the indolo­[2,3- b ]­quinoxaline scaffold, with a focus on enhancing solubility and H-cell cycling stability. Previous studies have suggested the use of tetraalkylammonium groups and glycol ethers to enhance the solubility of ROMs . We first incorporated the solubilizing groups into the core through N -alkylation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by these results, we proceeded to study the structure–property relationships for this class of anolytes in order to identify next-generation derivatives based on the indolo­[2,3- b ]­quinoxaline scaffold, with a focus on enhancing solubility and H-cell cycling stability. Previous studies have suggested the use of tetraalkylammonium groups and glycol ethers to enhance the solubility of ROMs . We first incorporated the solubilizing groups into the core through N -alkylation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested the use of tetraalkylammonium groups and glycol ethers to enhance the solubility of ROMs. 57 We first incorporated the solubilizing groups into the core through Nalkylation. Ammonium salt (5b) and glycol ether derivatives 5c−e were synthesized through our convergent synthetic route in excellent yield (91−93%; see the SI).…”
Section: Study Of the Relationship Between The Structure Of Indolo[23...mentioning
confidence: 99%
“…Carboxylic acid groups tend to dissociate only above a pH of approximately 4.5, and so in acidic solutions their solubilisation effect is less dramatic. [45] Quaternary amine groups and sodium ions are isoelectronic, which may help explain the high solubilisation often seen for aminated ROMs. [44] A quaternary amine substituted TEMPO has a water solubility of 3.2 mol L À 1 , compared to 2.5 mol L À 1 for TEMPO with a sodium carboxylate substituent at the same position.…”
Section: Solubilitymentioning
confidence: 99%
“…This has been achieved through the development of "waterin-Li salt" and "water-in-ionic liquid" electrolyte systems. [108,117] "Water-in-ionic liquid" electrolytes involve the incorporation of ionic liquids into water to create stable electrolyte solutions with extended electrochemical stability windows. [118,119] Ionic liquids, which are organic salts with low volatility, can offer higher thermal stability and wider electrochemical stability ranges compared to traditional aqueous electrolytes.…”
Section: Wide Electrochemical Potential Windowmentioning
confidence: 99%